A Base Nacional Comum Curricular do Ensino Médio e as diferentes expressões das diversidades: um estudo sobre invisibilidades e exclusão - ALMEIDA, NATALIE DE CASTRO (2022)
The research examines the curricular conceptions referring to the themes of diversities in the BNCC (Base Nacional Comum Curricular) of Brazilian High Schools, and its general objective was to identify and analyze presences, invisibilities and the silencing of themes related to sexual, gender and ethnic ethnic diversities. cultures in the document. The research assumes the urgency of discussing the diversities present in Brazilian school environments and the ineffectiveness of official curricular contents in the face of multiculturalism and sexual and gender diversities. In the methodological scope, the research sought to approach the object of investigation from its quantitative and qualitative dimensions, and mentions of the diversities in the items of each skill and competence of the BNCC document and their respective absences were identified. The discussion of the results took place from the theoretical bases explained and was based on the perspective of Laurence Bardin's content analysis. Data analysis allowed us to identify, in general, that the theme of diversities - gender, sexual and ethnic-racial - is little mentioned in the competences of the areas of Languages and their technologies, Natural Sciences and their technologies and Human Sciences and their technologies. The research findings showed that only 4 (four) of the 31 (thirty-one competencies) highlighted the theme of diversity, which corresponds to an insignificant portion in relation to the totality of the contents listed in the document descriptions. Furthermore, among the 183 (one hundred and eighty-three) skills of the different areas of knowledge, in 133 (one hundred and thirty-three) there is no mention of the different expressions of diversities. It was concluded that the theme of diversities within the BNCC, a document that guides educational practices in the country, is excluding and tends to make sexual, gender and ethnic-racial diversities invisible in the official Brazilian curriculum.